Pipeline risk management manual ideas, techniques, and resources - Muhlbauer, W. Kent. (Amsterdam ; Boston : Elsevier, 2004)
Here's the ideal tool if you're looking for a flexible, straightforward analysis system for your everyday design and operations decisions. This new third edition includes sections on stations, geographical information systems, "absolute" versus "relative" risks, and the latest regulatory developments. From design to day-to-day operations and maintenance, this unique volume covers every facet of pipeline risk management, arguably the most important, definitely the most hotly debated, aspect of pipelining today. Now expanded and updated, this widely accepted standard reference guides you in managing the risks involved in pipeline operations. You'll also find ways to create a resource allocation model by linking risk with cost and customize the risk assessment technique to your specific requirements. The clear step-by-step instructions and more than 50 examples make it easy. This edition has been expanded to include offshore pipelines and distribution system pipelines as well as cross-country liquid and gas transmission pipelines. The only comprehensive manual for pipeline risk managementUpdated material on stations, geographical information systems, "absolute" versus "relative" risks, and the latest regulatory developmentsSet the standards for global pipeline risk management.
Acknowledgements ... -- Risk: Theory and Application; Risk Management Process; Third Party Damage Index; Corrosion Index; Design Index; Incorrect Operations Index; Leak Impact Index; Data Management and Analyses; Additional Risk Modules; Service Interruption; Distribution Systems; Offshore Pipeline Systems; Stations and Surface Facilities; Absolute Risk; Risk Management.
Includes bibliographical references and index.
Keywords: Pipelines -- Safety measures -- Handbooks, manuals, etc; Pipelines -- Reliability -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc